How Noscapine metabolise Heme? - Singh, Prashant; Chandra, Ramesh; Singh, Harpal; Chandra, Ankush; K. Dass, Sujata (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Noscapine (NOS) is being used as an antitussive drug for a long time has been recently discovered as a novel tubulin binding, antiangiogenic anticancer drug that cause cell cycle arrest and induces apoptosis in cancer cells both in vitro as well as in vivo. It is a weak base (pKa~7.8) with 44.69 % absolute bioavailability and half-life of 1.33 h by oral route and requires relatively high doses of NOS (ED50~300 mg/kg bwt) for induction of anticancer activity. In the present study, we conducted experiments, wherein, noscapine was administered according to a dose schedule of 5 mg/kg bwt, 10 mg/kg bwt, 20 mg/kg bwt, 50 mg/kg bwt, 100 mg/kg bwt and 250 mg/kg bwt. Glutathione S-Transferase multigene family plays a critical role in the cellular protection. Toxicity evaluation has yielded that noscapine, do not impinge renal or hepatic toxicity at the dosing regimen (5 mg/kg bwt, 10 mg/kg bwt, 20 mg/kg bwt, 50 mg/kg bwt, 100 mg/kg bwt and 150 mg/kg bwt) undertaken during the course of study. Our results depicted that the antioxidant defense system thereby offering cellular protection.